2(3x-5)-4x=2x+7

Simple and best practice solution for 2(3x-5)-4x=2x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-5)-4x=2x+7 equation:


2(3x-5)-4x=2x+7

We simplify the equation to the form, which is simple to understand
2(3x-5)-4x=2x+7

Reorder the terms in parentheses
+(+6x-10)-4x=2x+7

Remove unnecessary parentheses
+6x-10-4x=+2x+7

We move all terms containing x to the left and all other terms to the right.
+6x-4x-2x=+7+10

We simplify left and right side of the equation.
0x=+17

0=17

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 12(2x+1)=144 | | 6(1+5n)-5(1+2n)=1 | | 8(9-x)= | | 7x-10y=6 | | 6p+3r=10 | | 3x+27=12y-10 | | 2x+13=28 | | 21x-9=5y+11 | | 72-6h=58 | | 135=-5+7(2a+4) | | 3+1(4(19)+1)=5(19-3) | | -5b+12=-3 | | 5x+2y-6z=450 | | y-1.4=1.9 | | 7x+3(4c-1)=-79 | | 12.1-a=8 | | 8k+7=9 | | 8k+7=9whatisk | | 43=7-4h | | 2n+6n= | | 4-5x+4=3x | | 22n+15=32n+3 | | 4(x+12)+2=9x | | (X-5)(X+2)=(X+4)(X-3) | | x^3+9x^2+18=0 | | 20-4y+11y=3 | | 2=-z/3 | | 15+4a=9a | | -5x+10y=-35 | | -1/4(-4-2x)=-12 | | 4*1(x+2)(2x+2)=x | | 2-6X=7-6X |

Equations solver categories